Association between physical activity and body posture: a systematic review and meta-analysis - Mohammad Salsali; Rahman Sheikhhoseini; Parisa Sayyadi; Julie A. Hides; Mahdis Dadfar; Hashem Piri (BMC, 2023)
Abstract Objective To estimate the possible associations between posture and physical activity (PA). Design A systematic review and meta-analysis. Data sources The search was conducted in seven databases (PubMed, Web of Science, SportDiscus, EMBASE, Scopus, Cochrane Library, and CINAHL) for studies published from inception to January 2023. Eligibility criteria for selecting studies Studies were required to meet following criteria: (1) study design: cross-sectional, case control and cohort studies. (2) Participants: people of all ages without any diagnosed diseases. (3) Exposure and outcome: studies that examined the possible effect or correlations between PA, physical inactivity, physical exertion and human body posture. Results Sixteen cross-sectional studies, two cohort studies and one case control study involving a total of 16772 participants aged from 6 to 79 years were included. Correlational studies showed that there was a significant relationship between PA and posture (C = 0.100, CI 95% = 0.012-0.186). However, regression studies demonstrated that there was not a significant association between PA and posture (C = 1.00, CI 95% = 0.998-1.002). Three studies investigated the association between PA and the lumbar lordosis and showed that there was not a significant association between the lordosis and PA (CI 95%: -0.253-0.048, P = 0.180). In addition, four studies showed that there were not any associations between scoliosis and PA (CI 95%: 0.819, 1.123, P = 0.607). The evidence of heterogeneity and publication bias was found among all analyzed data (P < 0.05). Also, meta regression was used for age and BMI and the results were not significant. Conclusion Although a weak correlation was shown to exist between PA and human posture, the odds ratio indicated that there was not a significant association between PA and human posture. The lack of a significant relationship may indicate that multiple biopsychosocial factors may be involved in human posture. In summary, our study highlights the need for caution when interpreting the results of meta-analyses, particularly when there is significant heterogeneity and publication bias in the included studies.